Association of postural orthostatic tachycardia syndrome, hypermobility spectrum disorders, and mast cell activation syndrome in young patients; prevalence, overlap and response to therapy depends on the definition - Yao, Lilian; Subramaniam, Kavya; Raja, Katherine M.; Arunachalam, Abi; Tran, Aubrey; Pandey, Tripti; Ravishankar, Sahana; Suggala, Sahan; Hendrickson, Caitlyn; Maxwell, Andrew J. (Frontiers in Neurology, 2025)
BackgroundThe close association of syndromes of orthostatic intolerance with and without postural orthostatic tachycardia syndrome (POTS) with Joint Hypermobility Disorders (JHD) including Hypermobility Spectrum Disorder (HSD) and hypermobile Ehlers Danlos Syndrome (hEDS) and with Mast Cell Activation Syndrome (MCAS) is now firmly established. However, the prevalence of each entity relative to the other is not well established and is affected greatly by the various definitions used for each syndrome. Use of restricting definitions for each syndrome can be problematic in the clinical setting as it under-estimates the presence of disease, thereby preventing clinicians from considering potentially helpful therapeutic options.MethodsA retrospective review of the clinical records of 100 young patients meeting POTS criteria was undertaken to determine the frequency of HSD, near-hEDS, and hEDS as well as the frequency of MCAS using consensus-1, conservative consensus-2, and clinical criteria regardless of lab support. Effectiveness of MCAS therapies was assessed in relation to the method of MCAS diagnosis.ResultsFrom records of 392 patients with orthostatic intolerance syndromes, 100 patients met POTS criteria. The frequency of JHD ranged from 13% using strict criteria of hEDS to 34% using HSD Criteria. The frequency of MCAS ranged from 2% using consensus-1 criteria, to 37% using conservative consensus-2 criteria, to 87% using clinical criteria. Patients diagnosed by clinical criteria with or without the aid of labs responded to therapy similarly to those diagnosed with stricter criteria.ConclusionUsing overly strict criteria to diagnose conditions which have a high prevalence of co-occurrence misses opportunities for potential therapeutic strategies.